Detection of Bioactive Compounds Produced by in Vitro Culture of Jojoba Plants (Simmondsia chinesi (Link) Schn.) Using GCMS and FTIR - Aman H. A. Althuluth; Aqeel A. Suhaim; Murtadha S. Auda (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The jojoba tree is economically important plant due to its high contains of oil and its various industrial, commercial and medical applications. A practical experiment was carried out to determine the optimal combination of plant growth regulators affecting the response of transplanted buds to unfolding, growth and callus induction on the formed explants. The study was conducted in the Plant Tissue Culture laboratory at the College of Agriculture-University of Basrah. Apical shoots were used to produce the initial callus when cultured on MS nutrient medium with combinations of plant growth regulators (0.5, 1 and 2 mg L-1 NAA and 1, 2.5 and 5 mg L-1 TDZ). The quality of the formed callus and the most important secondary compounds were analyzed using Gas chromatography–mass spectrometry (GC–MS)and Fourier-transform infrared spectroscopy (FTIR).The MS media(murashige and skoog) supplemented with 1 mg L-1 NAA + 2.5 mg L-1 TDZ and 2 mg L-1 NAA + 5 mg L-1 TDZ was most effective for callus formation, with the short period of time and the highest percentages of callus formation and fresh weight.GC-MS analysis identified various active compounds in the jojoba plant callus. The callus tissue contained a wide range of secondary metabolic compounds, including ethylene diol, sitosterol, vaccenic acid and ethyl ester methyl mannose, which all exhibit antioxidant activity.FTIR method was integrated to the spectrophotometric system to detect characteristic peak values and functional groups. Chemical compounds included the main functional groups such as phenols, alkanes, amine salts, benzenoid and sulfoxide compounds, primary amine groups and a class of halocarbon compounds. The jojoba plant can be propagated by ex vivo under the influence of plant growth regulators, producing secondary and chemical compounds significant in industrial and medical applications.